Keaktifan Sekolah Lansia untuk Meningkatkan Kualiatas Pembelajaran dan Posyandu Lansia di Desa Liprak Wetan Kecamatan Banyuanyar - Indi Wardah; Irna Tanti (Kalam Nusantara Institute, 2026)
The purpose of making this article is to complete the PKM assignment which uses the ABCD method which is useful for improving the health and memory of the elderly. We have taught several letters and numbers as well as reading and exercise for the elderly as well. Elderly school is a learning for people whose age is sustainable or called elderly. Elderly is the final stage of development in the flow of human life which is at risk to their health. To improve the V quality of life of the elderly, they can hold elderly posyandu activities. The purpose of the elderly school is to increase enthusiasm for the elderly in dealing with life's turmoil, to train the brain and restore memories for the elderly (elderly). The elderly must also do physical activity, namely by doing reading and writing, volunteering.